Students' Perception at the Use of Padlet in Linguistics Class - Choiril Anwar; Kurniawan Yudhi Nugroho; Idha Nurhamidah (NOTION: Journal of Linguistics, Literature, and Culture, 2019)
This study aims at investigating students’ perceptions of the use of Padlet in the class of Introduction to Functional Linguistics. The population of this study was a class of 2014 batch student of English Language Education program at Sultan Agung Islamic University (UNISSULA) Semarang with a sample of 28 people. This research is in the form of qualitative descriptive design. The data collection method uses observations and questionnaire. The data is then analyzed using interpretive descriptive analysis. The specific target to be achieved in this study is that by knowing students' perceptions of the use of Padlet, then this result can be used as a reference for the Faculty of Language and Communication Science and other faculties in the UNISSULA environment to improve the performance and quality of service to students especially in the learning and teaching process. In addition, the results of this study can also be a reference for both the Study Program and the Faculty to review the curriculum that has been implemented so far. From the data obtained through questionnaires distributed to 28 students of the English Language Education Study Program at the Faculty of Languages and Communication Science of Sultan Agung Islamic University Semarang in the class of 2014/2015, researchers can conclude that these students have very diverse perceptions in the use of Padlet media in learning Introduction to Functional Linguistics. To be sure, most students really positively appreciate the use of this media in linguistic learning in general